Pengaruh Penggunaan Pupuk Kompos Terhadap Pertumbuhan Kacang Tanah (Arachis hypogaea) di Lahan Organik - Sari, Evi Yunita; Yuriansyah; Sekar Buana, Arum; Septiana (J-Plantasimbiosa, 2025)
Organic farming is an environmentally friendly cultivation system that prioritizes natural ingredients and avoids the use of synthetic chemicals. To support peanut growth, this system relies on compost as a source of nutrients. Compost is believed to be rich in natural nutrients and can improve soil conditions. The proper use of compost is expected to increase peanut productivity in Indonesia, which is currently still low. The purpose of this study was to determine the effect of compost fertilizer dosage on the growth and yield of peanut plants. This study used a Completely Randomized Design (CRD), with one factor, namely the compost fertilizer dosage, repeated 3 times. The treatment consisted of several compost fertilizer dosages, namely C0 without compost; C1 compost 20 ml/L; C2 compost 40 ml/L; C3 compost 60 ml/L. The results of this study were that the C1 dosage (20 ml/L) was the most optimal for vegetative growth, producing much better plant height compared to other dosages, and pod weight (yield): the C3 dosage (60 ml/L) was the most effective for the generative phase, producing significantly the highest pod weight. Keywords: Compost, Dosage, Organic, Peanuts, Production